Lozovanu, D., Delinschi, A., Kahl, T. and Prishchepov, A. (eds.): Gagauziya (Gagauz Yeri) Avtonom Bölgesi Atlasi / Atlas of ATU Gagauzia (Gagauz Yeri) - Nemerkényi, Zsombor; Tátrai, Patrik (Hungarian Geographical Bulletin, 2014)
-